2013
DOI: 10.1016/j.bpj.2012.11.3807
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Niche Structure as an Inherent Cause of Undulating Epithelial Morphologies

Abstract: The spatial organization of stem cells into a niche is a key factor for growth and continual tissue renewal during development, sustenance, and regeneration. Stratified epithelia serve as a great context to study the spatial aspects of the stem cell niche and cell lineages by organizing into layers of different cell types. Several types of stratified epithelia develop morphologies with advantageous, protruding structures where stem cells reside, such as rete pegs and palisades of Vogt. Here, multistage, spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 55 publications
2
21
0
Order By: Relevance
“…How this arises is a matter of debate ranging from a proposed ‘spatial buckling’ model to a somewhat more active establishment of shape, involving defining matrix stiffness and spatial mechanics. In silico modeling that takes into account aspects of both hypotheses supports the notion that crypt formation along a basal lamina that is free-moving (as expected during development or tissue repair) would support an undulating morphology, while basal lamina attachment to an underlying matrix would in effect ‘stiffen’ the environment and support more regular patterning [97]. …”
Section: Tension At the Tissue Levelmentioning
confidence: 95%
See 1 more Smart Citation
“…How this arises is a matter of debate ranging from a proposed ‘spatial buckling’ model to a somewhat more active establishment of shape, involving defining matrix stiffness and spatial mechanics. In silico modeling that takes into account aspects of both hypotheses supports the notion that crypt formation along a basal lamina that is free-moving (as expected during development or tissue repair) would support an undulating morphology, while basal lamina attachment to an underlying matrix would in effect ‘stiffen’ the environment and support more regular patterning [97]. …”
Section: Tension At the Tissue Levelmentioning
confidence: 95%
“…Furthermore, to treat diseases that include an element of defective mechanotransduction, putative compounds must be tested in the appropriate 3D matrix mechanics to accurately predict responses [116], and active efforts to develop compounds that selectively target key elements of the mechanotransduction pathway will be critical [117]. New mechanistic insights into how cells sense and respond to tissue mechanics will follow from the widespread implementation of in silico modeling [118] to develop complex cell-cell and cell-matrix models [92,97,106,119], and the development of 3D models to systematically tease apart the influence of diverse matrix mechanical properties, biomolecules, and genetic alterations on cell behaviors and fate in a controlled manner [120-123]. …”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…These population dynamic models could include age structure (29), evolution (27,30), and stochasticity (30,31); and these models could also be applied to the regulation of cancer (32). Studies based on spatial modeling have found that diffusive and regulatory molecules involved in feedback mechanisms regulating the differentiation capabilities of the cells are important in maintaining the stem cell niche and shaping tissue stratification (33,34).…”
mentioning
confidence: 99%
“…[42][43][44][45][46][47] These tissue borders are defined by the presence of basement membranes (BM) which separate cells from the surrounding ECM. Furthermore, the BM has been reported to create niches of stem cells between the basal lamina and various tissues, including skeletal muscle, 48 epithelium, 42,[49][50][51][52] hair follicles, 50,53,54 peripheral nerves, 55 blood vessels, 56 bone 57-61 and teeth. 62 A recent discovery that stem cells are generated during mesenchymal to epithelial transitions provides further support for this hypothesis.…”
Section: Tissue As a Repository Of Cellular History Affording Memory mentioning
confidence: 99%